Indices de structures spatiales des îlots de forêts denses dans la région des Monts Kouffé - Inoussa Toko Mouhamadou; Fatou Touré; Ismaila Toko Imorou; Brice Sinsin (VertigO)
Monts Kouffe's region concerns here Monts Kouffe's forest reserve and its south suburb. In Benin, Monts Kouffe forest reserve undergoes anthropic pressures which are galloping population growth, a shifting cultivation, anarchy meadow and poaching, unfair forestry woods using, forested ecosystems' dysfunction and loss of biodiversity. The aim of this study is to characterize Monts Kouffe forest reserve and periphery’s dense forests islands in order to present their spatio-temporal dynamic. The adopted methodology is based on Remote Sensing, Cartography and Landscape Ecology techniques. From 1986 Landsat TM and 2006 Landsat ETM+ images for 30 m spatial resolution, these allowed the computation of spatial indexes as number of spots (dense forests islands), total area of spots, dominance, average area, spots areas’ diversity and, shape index.